Anterior Cruciate Ligament–Derived Stem Cells Transduced With BMP2 Accelerate Graft-Bone Integration After ACL Reconstruction. (March 2017) - Kawakami, Yohei; Takayama, Koji; Matsumoto, Tomoyuki; Tang, Ying; Wang, Bing; Mifune, Yutaka; Cummins, James H.; Warth, Ryan J.; Kuroda, Ryosuke; Kurosaka, Masahiro; Fu, Freddie H.; Huard, Johnny
Background: Strong graft-bone integration is a prerequisite for successful graft remodeling after reconstruction of the anterior cruciate ligament (ACL) using soft tissue grafts. Novel strategies to accelerate soft tissue graft-bone integration are needed to reduce the need for bone-tendon-bone graft harvest, reduce patient convalescence, facilitate rehabilitation, and reduce total recovery time after ACL reconstruction. Hypothesis: The application of ACL-derived stem cells with enhanced expression of bone morphogenetic protein 2 (BMP2) onto soft tissue grafts in the form of cell sheets will both accelerate and improve the quality of graft-bone integration after ACL reconstruction in a rat model. Study Design: Controlled laboratory study. Methods: ACL-derived CD34+ cells were isolated from remnant human ACL tissues, virally transduced to express BMP2, and embedded within cell sheets. In a rat model of ACL injury, bilateral single-bundle ACL reconstructions were performed, in which cell sheets were wrapped around tendon autografts before reconstruction. Four groups containing a total of 48 rats (96 knees) were established (n = 12 rats; 24 knees per group): CD34+BMP2 (100%), CD34+BMP2 (25%), CD34+ (untransduced), and a control group containing no cells. Six rats from each group were euthanized 2 and 4 weeks after surgery, and each graft was harvested for immunohistochemical and histological analyses. The remaining 6 rats in each group were euthanized at 4 and 8 weeks to evaluate in situ tensile load to failure in each femur-graft-tibia complex. Results: In vitro, BMP2 transduction promoted the osteogenic differentiation of ACL-derived CD34+ cells while retaining their intrinsic multipotent capabilities. Osteoblast densities were greatest in the BMP2 (100%) and BMP2 (25%) groups. Bone tunnels in the CD34+BMP2 (100%) and CD34+BMP2 (25%) groups had the smallest cross-sectional areas according to micro–computed tomography analyses. Graft-bone integration occurred most rapidly in the CD34+BMP2 (25%) group. Tensile load to failure was significantly greater in the groups containing stem cells at 4 and 8 weeks after surgery. Tensile strength was greatest in the CD34+BMP2 (100%) group at 4 weeks, and in the CD34+BMP2 (25%) group at 8 weeks. Conclusion: ACL-derived CD34+ cells transduced with BMP2 accelerated graft-bone integration after ACL reconstruction using soft tissue autografts in a rat model, as evidenced by improved histological appearance and graft-bone interface biology along with tensile load to failure at each time point up to 8 weeks after surgery. Clinical Relevance: A primary disadvantage of using soft tissue grafts for ACL reconstruction is the prolonged time required for bony ingrowth, which delays the initiation of midsubstance graft remodeling. The lack of consistent correlation between the appearance of a "healed" ACL on postoperative magnetic resonance imaging and readiness to return to sport results in athletes being released to sport before the graft is ready to handle high-intensity loading. Therefore, it is desirable to identify strategies that accelerate graft-bone integration, which would reduce the time to biologic fixation, improve the reliability of biologic fixation, allow for accelerated rehabilitation, and potentially reduce the incidence of early graft pullout and late midsubstance failure.